Optimal Surgical Approach for Bilateral Congenital Lobar Emphysema: Evaluating a Staged, Response Based Approach - Shreyas Krishnamurthy; Arvind Sinha; Siva Kamesh; Kirtikumar J. Rathod; Rahul Saxena; Manish Pathak (Journal of Indian Association of Pediatric Surgeons)
Management of bilateral congenital lobar emphysema (CLE) is challenging and only a few isolated cases are available in the literature for guiding surgeons in managing such cases. We recently managed a child with bilateral CLE and realized that there is an extreme dearth of data available in the literature to guide a surgeon on the management of children with bilateral CLE. We performed a systematic review of the available literature and share our understanding from the same. A 10-month-old child presented to our emergency room with intermittent episodes of tachypnea and respiratory distress since birth. Computed tomography of the chest was suggestive of CLE of the left upper and the right middle lobe (RML) with mediastinal shift toward the right. Left posterolateral thoracotomy and left upper lobectomy were performed and the child was kept in follow-up for RML pathology. After 4 uneventful months, the child was readmitted with respiratory distress. Repeat imaging demonstrated continued RML hyperinflation with atelectatic changes in the adjacent lobes and he subsequently underwent RML ctomy. Our literature review suggests that the infants tolerate sequential thoracotomies better than the single-staged bilateral thoracotomies. Literature suggests that up to a fifth of the patients might not require the second surgery based on the clinical condition of the child on careful follow-up. Our case report and review support staged and a response-based approach to bilateral CLE has a promising outcome.